ANALISIS KUALITAS AIR GAMBUT DAN KELUHAN KESEHATAN PADA MASYARAKAT DI DUSUN PULO GOMBUT DESA SUKA RAME BARU KECAMATAN KUALA HULU KABUPATEN LABUHAN BATU UTARA TAHUN 2012 - Dipo Satryo Suhendra; Irnawati Marsaulina; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2013)
nalysis of peat water quality and health complaint at community on Pulo Gombut Orchard Suka Rame Baru Village Kuala Hulu Subdistrict Labuhan Batu Utara Regency in 2012. Peat water was one of water source which used by Dusun Pulo Gombut Desa Suka Rame Baru Kecamatan Kuala Hulu Kabupaten Labuhan Batu people. In order to assure water quality which used by people is safety therefore need a water quality control. The purpose of this study is to analyze peat water quality for physic quality, biological quality, chemical quality and health complain which sequenced by peat water used. The method used was descriptive with 136 population. Sampling based on random sampling thus got 58 sample. Water sampling points taken at the upstream, midstream and downstream with depth 1,5 m. The result are obtained that physic quality of peat water each in the upstream, midstream and downstream, smell parameter (not smell), TDS (35 - 36 mg/L), temperature (27,7 - 27,90C) and taste (not taste) completed I class standard, but colour parameter (419 - 430 Pt.Co), turbidity (37 - 236 NTU) uncompleted I class standard. Chemical quality, Cd parameter (0,00429 - 0,00476 mg/L) and sulfate (17 - 21 mg/L) completed I class standard, but pH parameter (4,5 - 4,8), Fe (0,89662 - 0,93007 mg/L), Mn (0,17630 - 0,19402 mg/L) and BOD (15,73 - 16,27 mg/L) uncompleted I class standard. Biological parameter, total coliform parameter (79/100 - 130/100 ml) completed I class standard. Health complaints are suffered people, itching (72,4%), diarrhea (19,0%) and scaly skin (8,6%). So suggested to make water filter, use plengsengan latrines, cook water maturely and take a bath by using soap. Key words : peat water, physic quality, chemical quality, biological quality, health complaint